Pengaruh dinamika tutupan lahan terhadap fenomena Urban Heat Island di Kota Tegal - Luthfia Khairunnisa; Soedwiwahjono Soedwiwahjono; Erma Fitria Rini (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Land cover change driven by urbanization significantly affects surface temperature increases and the emergence of the Urban Heat Island (UHI) phenomenon in urban areas. Tegal as a developing coastal city, has experienced dynamic regional development that influences land cover patterns and surface temperature distribution. This study aims to analyze the impact of land cover dynamics on the UHI phenomenon in Tegal during the 2000–2024 period. A quantitative remote sensing approach was applied using Landsat 5 TM and Landsat 8 OLI imagery to extract Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Built-up Index (NDBI), along with supervised land cover classification. The relationship between land cover change and LST was examined using spatial regression models, namely Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR). The results indicate that agricultural land, vegetation canopy, and water bodies have a negative effect on surface temperature, while building density represented by NDBI contributes positively to temperature increases. The peak UHI intensity occurred in 2010, coinciding with intensified urbanization, and subsequently declined in 2024 due to the expansion of water bodies associated with seawater intrusion. Additionally, the spatial pattern of UHI shifted from areas near the port toward the southern part of the city, reflecting ongoing regional development dynamics. These findings provide important insights for regional development planning and climate adaptation strategies in coastal cities.